Understanding Consumer Preferences In Choosing Cosmetics: The Role Of Halal Lifestyle, Pricing, And Promotion - Ariyono, Kurniawan Yunus (Jurnal Ilmu Manajemen Advantage, 2023)
The cosmetics industry in Indonesia is currently experiencing rapid growth, encompassing both local and international products that are actively competing in the market. Wardah Cosmetics, a local brand, notably dominates the market share, particularly due to its halal image, making its products highly sought after. This research adopts an explanatory quantitative approach, employing a survey method involving questionnaires distributed to both Wardah consumers and students at ITB Widya Gama Lumajang. Purposive sampling was used to select respondents who had purchased Wardah cosmetics at least once, resulting in a sample size of 100 respondents. The data analysis involved multiple linear regression analysis. The statistical findings from this research reveal that, on a partial basis, both halal lifestyle and price significantly influence the purchasing decisions of consumers regarding Wardah cosmetic products. In contrast, promotional activities do not exhibit a significant effect on the decision-making process for purchasing Wardah cosmetic products. Additionally, when considering all three factors together (simultaneously), they collectively exert a significant influence on consumers' decisions to purchase Wardah cosmetic products, contributing to an overall influence of 53.8%.